The role of the parenchyma sheath and PCD during the development of oil cavities in Pterodon pubescens (Leguminosae-Papilionoideae) - Rodrigues, Tatiane Maria [UNESP]; dos Santos, Daniela Carvalho [UNESP]; Machado, Silvia Rodrigues [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
Pterodon pubescens cavities are constituted by lumen and uniseriated epithelium surrounded by multiseriate parenchyma sheath. We studied the development of secretory cavities, including the role of parenchyma sheath, using light and transmission electron microscopy. A Tunel assay was performed to verify whether programmed cell death (PCD) occurs during the process. The lumen is formed by schizogeny and lysigeny occur in later developmental stages of the secretory cavities. Ultrastructurally, epithelial cells in later developmental stages become dark and with sinuous walls: the protoplast becomes retracted and the cytoplasm shows low organelle definition. Degenerated cells are released toward the lumen. Our results showed that PCD occurs during later developmental stages of cavities and plays a critical role in functioning of these glands. New cells originated from the parenchyma sheath differentiate into secretory cells and replace those degenerated ones. This fact associated to PCD guarantees epithelium renovation during the secretory cycle and the maintenance of secretory activity of cavities. (C) 2011 Acadamie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Epithelium renovation; Oil cavity; Parenchyma sheath; Programmed cell death; Pterodon pubescens